COVID-19 Pandemic Knowledge & Perception: A Quiz Based Survey on Students in India - Pathania, Anita; Saini, Archana; Tandon, Sadhana (International Journal of Applied Sciences and Biotechnology, 2021)
Emergence and spread of COVID-19 pandemic which is caused by novel coronavirus (SARS-CoV-2) is threatening the whole world. The virus originated in bats and was transmitted to humans through unknown intermediate animal host in Wuhan, Hubei province, China in December 2019. Coronavirus disease 2019 (COVID-19) outbreak needed to be put to an end and we can do this by understanding the situation better. It was of prime importance that masses particularly youngsters should have maximum knowledge of this disease in detail to check its rapid spread. Thus, this study aimed to investigate the knowledge and perceptions of students about COVID-19. With this kind of awareness, each respondent updating one’s scientific realization about this deadly virus and how to cope with this. For this purpose, an online survey was conducted using a semi-structured questionnaire using a multiple-choice questions method. A total of 1,111 responses were received. total 840 (75.60%) students from different colleges/universities and 271 (24.39%) school students have participated in this survey. The responders had a moderate level of knowledge about the COVID-19 infection and adequate knowledge about its preventive aspects. The attitude towards COVID-19 showed students' willingness to follow government guidelines on quarantine and social distancing. There is a need to intensify the awareness and address the issues of safety of students about this COVID-19 pandemic as this is still spreading at an alarming rate in India. Int. J. Appl. Sci. Biotechnol. Vol 9(2): 133-137.